GmABR1 encoding an ERF transcription factor enhances the tolerance to aluminum stress in Arabidopsis thaliana - Wang, Hongjie; Li, Cheng; Wang, Lidan; Zhong, Hongying; Xu, Xin; Cheng, Yanbo; Nian, Hai; Liu, Wenhua; Chen, Pei; Zhang, Aixia; Ma, Qibin (Frontiers in Plant Science, 2023)
The ethylene response factor (ERF) transcription factor, one of the largest transcription factor families in plants, are involved in biological and abiotic stress response and play an important role in plant growth and development. In this study, the candidate gene GmABR1 from the soybean inbred line Zhonghuang24 (ZH24)×Huaxia 3 (HX3) was cloned and investigated its aluminum (Al) tolerance. GmABR1 protein has a conserved domain AP2, which is located in the nucleus and has transcriptional activation ability. The results of real-time fluorescence quantitative PCR (qRT-PCR) showed that GmABR1 gene presented a compositive expression pattern rich in the root tip, stem and leaf tissues of HX3. After Al stress, the GmABR1 transcript was significantly increased in the roots. The transcription amount of GmABR1 in the roots of HX3 treated with 50 µM AlCl3 was 51 times that of the control. The GmABR1 was spatiotemporally specific with the highest expression levels when Al concentration was 60 µM, which was about 36 times that of the control. The results of hematoxylin staining showed that the root tips of GmABR1-overexpression lines were stained the lightest, followed by the control, and the root tips of GmABR1 RNAi lines were stained the darkest. The concentrations of Al3+ in root tips were 207.40 µg/g, 147.74 µg/g and 330.65 µg/g in control, overexpressed lines and RNAi lines, respectively. When AlCl3 (pH4.5) concentration was 100 µM, all lines were significantly inhibited. The taproot elongation of wild-type (WT) lines was 69.6%, and that of GmABR1 transgenic lines was 85.6% which was significantly higher than that of WT. When treated with Al, the content of malondialdehyde (MDA) in leaves of wild-type increased to 3.03 µg/g, while that of transgenic Arabidopsis increased from 1.66-2.21 µg/g, which was lower than that of WT. Under the Al stress, genes related to Al response such as AtALMT1 and AtMATE, and genes related to ABA pathway response such as AtABI1, AtRD22 and AtRD29A were regulated. We hypothesized that GmABR1 may jointly regulate plant resistance to Al stress through genes related to Al response and ABA response pathways.